The Ability of Students at Dharma Putra Kindergarten in Recalling English Vocabularies - Enno Ariestha, Gusti Ayu Putu (Humanis; Vol 22 No 1 (2018)DO - 10.24843/JH.2018.v22.i01.p36, 2018)
The demand of using English as a mean of communication caused Indonesian government has drawn up English as a foreign language that should be mastered by the students. To acquire a very good skill of English, the children were int r oduced English in a very young age by parents and teachers. The present study conducted to find out the ability of students at Dharma Putra Kindergarten in recalling English vocabularies and the significant factors influence them. The data in this study collected through observation, direct interview and questionnaire. The observation is aimed to know the students’ daily activities in the school. The direct interview used to find out the ability of students in recalling English vocabularies and the questionnaire used to identify the significant factors influence the students ability in recalling the English vocabularies. The questionnaire for the parents consisted of 18 questions about the significant factors affect the students’ vocabularies. Furthermore, the obtained data analyzed quantitatively and qualitatively. The data from direct interview was analyzed by using the evaluation from Amirono and Daryanto (2016) and the data from questionnaire was analyzed by using theory from Harmer (2001) about motivation. The result of the interview shows that the students’ average score in recalling English vocabulary is 3.31 %, indicating that the ability of the students at Dharma Putra Kindergarten in recalling English vocabularies is Excellent. The teacher, parents, teaching method and the school environment become significant facto r s which influence the ability of students in recalling English vocabularies.